ART IS THE SYMBOL OF BEAUTY (American Journal of Pedagogical and Educational Research, 2026)
Aesthetic education is, first of all, the development of beauty, creative ability, and reflective thinking. Artistic education is essential for every individual regardless of their profession, as it contributes to the formation of personality. The richer a person’s aesthetic experience, the more refined their taste and the clearer their moral choices become, the freer they are as an individual. The study of the history of fine arts represents an introduction to universal heritage and culture. It is a vivid, understandable, and meaningful narrative — a bridge across centuries and nations.A teacher should care about the general humanitarian and artistic knowledge of students. The curriculum includes the main concepts of types and genres of fine arts, the principal stages of the history of Western European art from the ancient world to the modern era, the art of Eastern countries, and the art of Uzbekistan. While discussing the development of art both historically and within specific periods, the teacher should examine every artistic phenomenon in connection with the historical circumstances that shaped it.The methodology of instruction should be directed toward the development of creative abilities, knowledge, and emotional activity. The forms of classes may vary, including storytelling, debates, lectures, discussions, films, excursions, and others. Students learn to work with literature and develop the ability to independently analyze works of art. This curriculum defines the scope and content of knowledge while preserving the teacher’s right to organize the material creatively: rearranging topics, comparing works from different sections, and so forth. It is recommended that students record material in notebooks and supplement it with comments and independent work assignments. Notebooks should be checked regularly. During lessons, technical teaching aids should be widely used.Along with the general characteristics of artistic movements and styles, special attention should be given to the biographies of the most important artists such as Leonardo da Vinci, Raphael, Michelangelo, Titian, Albrecht Dürer, Caravaggio, Hieronymus Bosch, Peter Paul Rubens, Rembrandt, Antoine Watteau, Jean-Baptiste-Siméon Chardin, Diego Velázquez, Nicolas Poussin, Francisco Goya, Eugène Delacroix, J. M. W. Turner, Édouard Manet, Claude Monet, Pierre-Auguste Renoir, Edgar Degas, Vincent van Gogh, Henri Matisse, Alexander Ivanov, Orest Kiprensky, Ural Tansykbayev, Pavel Benkov, and Rahim Ahmedov.